Victimization experiences and well-being in adulthood: A systematic review and meta-analysis - Ferreira, Célia Isabel Lima (2022)
Scientific research has explored the impact of violence during adulthood on psychopathology. Fewer efforts have been made from a positive theoretical framework, and no systematic evidence has been provided. This manuscript describes a literature review and meta- analysis on the relationship between victimization experiences and well-being in adulthood. A literature review was performed, and 27 studies met the inclusion criteria for the systematic review 16 for the meta-analysis. The meta-analysis yielded a medium and significant overall effect size (r = -.309, p < .001), which indicated that greater victimization experiences partly explain lower well-being outcomes. A set of theoretical and methodological issues are discussed, specifically considering the conceptualization of victimization and well-being as well as the studies design, sample characteristics, measures and data analysis. Derived from this integrative discussion, some recommendations are also provided for future research.